Increases in nitrogen use efficiency decrease nitrous oxide emissions but can penalize yield in sugarcane - Chalco Vera, Jorge Elías; Portocarrero, Rocio; Piñeiro, Gervasio; Acreche, Martin Moises (Springer, 2021)
Nitrogen (N) fertilization strategies focused on increasing nitrogen use efficiency (NUE) and decreasing nitrous oxide (N2O) emissions are important for sustainable crop production. In sugarcane, however, a joint assessment of NUE, N2O emissions and yield is still required. We aimed to establish, in a subtropical sugarcane cropping system, if variations in NUE (by decreasing rates or changing formulations of N fertilization) allow decreasing N2O emissions and, to what extent, yield is penalized. Four fertilization treatments were used: without fertilizer, with low and high urea fertilization (55 and 110 kg N ha−1) and with ammonium nitrate fertilization (110 kg N ha−1). There was a significant negative relationship between N2O emissions and NUE. At high N rates (110 kgN ha−1) ammonium nitrate produced 37% higher cumulative N2O emissions and 13 and 12% lower NUE and cane yield, respectively, than urea. The highest N2O emissions of the ammonium nitrate treatment occurred within 48 hs after N fertilization and were mainly associated with the direct addition of nitrate (NO3−–N). Results showed that, for the environmental conditions of Tucuman (Argentina), NUE above 160 kg of cane per kg of N available in soil penalized cane yield, whereas NUE below 140 kg of cane per kg of N available in soil penalized N2O emission abatement.